2000
DOI: 10.1084/jem.192.3.433
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Leukotriene B4Receptor in Mice Reveals Its Role in Inflammation and Platelet-Activating Factor–Induced Anaphylaxis

Abstract: Leukotrienes are derived from arachidonic acid and serve as mediators of inflammation and immediate hypersensitivity. Leukotriene B4 (LTB4) and leukotriene C4 (LTC4) act through G protein–coupled receptors LTB4 receptor (BLTR) and Cys-LTR, respectively. To investigate the physiological role of BLTR, we produced mice with a targeted disruption of the BLTR gene. Mice deficient for BLTR (BLTR−/−) developed normally and had no apparent hematopoietic abnormalities. Peritoneal neutrophils from BLTR−/− mice displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 25 publications
4
144
1
1
Order By: Relevance
“…Studies using mice with a disrupted BLT1 gene confirm that BLT1 functions in acute inflammation and immediate hypersensitivity as well as in leukocyte activations (45,46). The BLT1-signaling pathway involves activation of phosphoinositide-specific phospholipase C␤ via Bordetella pertussis toxin (PTX)-sensitive (G i/o ) and PTX-resistant (G 16 , G 14 ) G-proteins (29,47).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using mice with a disrupted BLT1 gene confirm that BLT1 functions in acute inflammation and immediate hypersensitivity as well as in leukocyte activations (45,46). The BLT1-signaling pathway involves activation of phosphoinositide-specific phospholipase C␤ via Bordetella pertussis toxin (PTX)-sensitive (G i/o ) and PTX-resistant (G 16 , G 14 ) G-proteins (29,47).…”
Section: Discussionmentioning
confidence: 99%
“…In animal models for arthritis, skin inflammation, and peritonitis, LTB 4 antagonists reduce clinical symptoms (18 -20). Moreover, in mice deficient for the LTB 4 receptor BLT1, the inflammatory response in a peritonitis model is significantly reduced, suggesting an important role for LTB 4 in PMN chemotaxis in vivo (21).…”
Section: P Olymorphonuclear Neutrophils (Pmn)mentioning
confidence: 99%
“…Recently, a second human receptor for LTB 4 (BLT2) was cloned and shown to have lower affinity for LTB 4 and wider tissue distribution (8,9). The recent development of mice with disrupted BLT1 suggests a major role for BLT1 in acute inflammation and immediate hypersensitivity as well as in leukocyte functions such as chemotaxis and firm adhesion to endothelium in response to LTB 4 (10,11). Devchand and collaborators (12) have also shown that LTB 4 can bind to the peroxisome proliferator-activated receptor ␣ with low affinity and may have a role in activating genes that terminate inflammatory processes.…”
Section: Leukotriene B 4 (Ltb 4 )mentioning
confidence: 99%